2010
DOI: 10.1093/aob/mcq123
|View full text |Cite
|
Sign up to set email alerts
|

Stem hypertrophic lenticels and secondary aerenchyma enable oxygen transport to roots of soybean in flooded soil

Abstract: Hypertrophic lenticels on the stem of soybean, just above the water surface, are entry points for O(2), and these connect to aerenchyma and enable O(2) transport into roots in flooded soil. Stems that develop aerenchyma thus serve as a 'snorkel' that enables O(2) movement from air to the submerged roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 33 publications
4
92
0
3
Order By: Relevance
“…For example, in soybean, aerenchyma arises through cell division of the phellogen to form a spongy parenchymaous cell layer between the cortex and epidermis (Thomas et al, 2005;BaileySerres and Voesenek, 2008). This arises after several days of waterlogging and enhances the aeration of roots and nodules necessary for growth and nitrogen fixation, respectively (Shimamura et al, 2010). The single cell layer cortex of Arabidopsis does not form aerenchyma, but waterlogging may promote the formation of lacunae in secondary xylem of the hypocotyl of mature rosettes (Mühlenbock et al, 2007), which could facilitate gas exchange.…”
Section: Morphological and Anatomical Adaptations That Increase Floodmentioning
confidence: 99%
“…For example, in soybean, aerenchyma arises through cell division of the phellogen to form a spongy parenchymaous cell layer between the cortex and epidermis (Thomas et al, 2005;BaileySerres and Voesenek, 2008). This arises after several days of waterlogging and enhances the aeration of roots and nodules necessary for growth and nitrogen fixation, respectively (Shimamura et al, 2010). The single cell layer cortex of Arabidopsis does not form aerenchyma, but waterlogging may promote the formation of lacunae in secondary xylem of the hypocotyl of mature rosettes (Mühlenbock et al, 2007), which could facilitate gas exchange.…”
Section: Morphological and Anatomical Adaptations That Increase Floodmentioning
confidence: 99%
“…Non spaces can form channels that are connected throughout the plant, and serve as routes of low resistance to the diffusion of gases and toxic products derived from the metabolism (Kozlowski 1997;Simone et al 2003;Shimamura et al 2010). Among the six species studied, only T. rosea formed aerenchyma in the roots and stem.…”
Section: Speciesmentioning
confidence: 99%
“…Secondary aerenchyma in the form of aerenchymatous phellem has been reported in several dicotyledonous wetland species when subjected to flooded conditions (Metcalfe 1931;Jackson 2006). Several lines of evidence show that the presence of these structures can facilitate the entry of oxygen to internal plant tissues (Shimamura et al 2010;Teakle et al 2011). Experiments with soybean (Glycine max) under flooding conditions showed that root growth was inhibited when the entry of atmospheric O 2 to the secondary aerenchyma through hypertrophic lenticels was prevented (Shimamura et al 2003).…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The aerenchyma formed in stem, roots and nodules improves gas exchange between the shoots and root system (Bacanamwo and Purcell, 1999b;Shimamura et al, 2003;Shimamura et al, 2010); the nodule nitrogen fixation is restored by the formed aerenchyma to some extent (Bacanamwo and Purcell, 1999b;Shimamura et al, 2002;Thomas et al, 2005). However, short-term waterlogging for several days (i.e., less than a week) in farm fi elds, did not lead to the development of adventitious roots or the formation of aerenchyma.…”
mentioning
confidence: 99%